Three-year long-term outcome of 458 naturalistically treated inpatients with major depressive episode: severe relapse rates and risk factors - Seemüller, Florian; Meier, Sebastian; Obermeier, Michael; Musil, Richard; Bauer, Michael; Adli, Mazda; Kronmüller, Klaus-Thomas; Holsboer, Florian; Brieger, Peter; Laux, Gerd; Bender, Wolfram; Heuser, Isabella; et al. (European archives of psychiatry and clinical neuroscience, 2014)
In randomized controlled trials, maintenance treatment for relapse prevention has been proven to be efficacious in patients responding in acute treatment, its efficacy in long-term outcome in “real-world patients” has yet to be proven. Three-year long-term data from a large naturalistic multisite follow-up were presented. Severe relapse was defined as suicide, severe suicide attempt, or rehospitalization. Next to relapse rates, possible risk factors including antidepressant medication were identified using univariate generalized log-rank tests and multivariate Cox proportional hazards model for time to severe relapse. Overall data of 458 patients were available for analysis. Of all patients, 155 (33.6 %) experienced at least one severe relapse during the 3-year follow-up. The following variables were associated with a shorter time to a severe relapse in univariate and multivariate analyses: multiple hospitalizations, presence of avoidant personality disorder, continuing antipsychotic medication, and no further antidepressant treatment. In comparison with other studies, the observed rate of severe relapse during 3-year period is rather low. This is one of the first reports demonstrating a beneficial effect of long-term antidepressant medication on severe relapse rates in naturalistic patients. Concomitant antipsychotic medication may be a proxy marker for treatment resistant and psychotic depression.